In vitro and in vivo effectiveness of essential oils against coccidia in Black Livorno chickens - Alessia Zoroaster; Marta Raffaelli; Manuela Diaferia; Fabrizia Veronesi; Margherita Marzoni Fecia di Cossato; Barbara Contiero; Roberto Marani; Antonio Frangipane di Regalbono; Stefania Perrucci (BMC Veterinary Research)
Abstract Background Coccidiosis remains a major challenge in poultry farming due to the drug-resistance phenomena in Eimeria strains and the possible risk of accumulation of anticoccidial residues in poultry-derived products. Essential oils (EOs) and their bioactive constituents are being considered for their potential role as alternative control strategies. The present study evaluated the in vitro efficacy of thymol, carvacrol, cinnamic aldehyde, eugenol, and a commercial EO blend (namely Energy Poultry, EP) against Eimeria spp., as well as the in vivo efficacy of thymol and EP (supplemented at 5 mg/kg and 50 mg/kg of feed, respectively) in growing chickens. Results In vitro assays demonstrated that thymol and carvacrol significantly disrupted oocyst integrity and inhibited sporulation at concentrations ≥ 2%, with maximal degeneration rates of 96% and 90%, respectively, at 10%. Cinnamic aldehyde reduced sporulation by 79%, whereas eugenol showed minimal efficacy. The potential synergistic effect between carvacrol and cinnamic aldehyde of EP resulted in a marked reduction in oocyst viability (~ 90%). Based on these findings, thymol and EP were selected for in vivo evaluation in a native Italian egg-type chicken breed, the Black Livorno. Despite not significant, dietary supplementation (thymol: 5 mg/kg; EP: 50 mg/kg) led to a reduction in oocyst per gram (OPG) values from day 78 onward compared to the control group in which the highest oocyst excretion persisting for an extended period. Growth performance (average daily gain and feed conversion ratio) was not affected, indicating no adverse effects of thymol and EP supplementation. Despite the presence of highly pathogenic Eimeria species (E. tenella, E. necatrix), no clinical signs were observed, probably due to the possible low parasitic burden and breed’s inherent resistance. Conclusions The obtained findings suggest that while evaluated EO constituents exhibited promising anticoccidial effects in vitro, their in vivo efficacy may be dose-dependent, influenced by infection pressure and host factors. Further research is warranted to optimise tested EOs inclusion levels and assess their long-term impact on coccidiosis control in poultry production systems.